2016
DOI: 10.1200/jop.2015.006619
|View full text |Cite
|
Sign up to set email alerts
|

ReCAP: Attitudes, Beliefs, and Awareness of Graduate Medical Education Trainees Regarding Palliative Care at a Comprehensive Cancer Center

Abstract: QUESTION ASKED: What are graduate medical education trainees' attitudes and beliefs regarding palliative care, what is their awareness of the availability and role of palliative care services, and does previous exposure to a palliative care rotation facilitate a better awareness of palliative care?SUMMARY ANSWER: A vast majority of oncology trainees perceived palliative care services to be beneficial for patient care (92%) and were supportive of mandatory palliative care training (74%). Surgical oncology train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
1
20
0
2
Order By: Relevance
“…We hypothesize that younger oncologists were (a) more familiar with the concept of early palliative care compared with their more senior colleagues, (b) more prepared to adopt new advances based on the literature, and (c) more willing to adhere to clinical practice guidelines. A recent survey found that medical oncology fellows at our institution who all had a 1‐month palliative care rotation had a higher level of awareness of the role of palliative care than fellows who did not have a rotation . This rotation offers an enriched opportunity for oncology trainees to gain a better understanding of the role of palliative care and to build a professional relationship with the palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that younger oncologists were (a) more familiar with the concept of early palliative care compared with their more senior colleagues, (b) more prepared to adopt new advances based on the literature, and (c) more willing to adhere to clinical practice guidelines. A recent survey found that medical oncology fellows at our institution who all had a 1‐month palliative care rotation had a higher level of awareness of the role of palliative care than fellows who did not have a rotation . This rotation offers an enriched opportunity for oncology trainees to gain a better understanding of the role of palliative care and to build a professional relationship with the palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…This requires that cancer professionals are familiar with the role of palliative care and comfortable in discussing palliative care considerations with their patients. However, attitudes to, and use of, palliative care services and approaches vary among oncology professionals and cancer services [28,29,30,31]. This is turn may affect the care received by patients and their quality of life in the end stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study exploring attitudes and beliefs among oncology trainees regarding palliative care, 67% believed that a mandatory palliative care rotation was important; those who had completed palliative care rotations were more aware of the role of palliative care services than those who had not done so (96% versus 74%). 541 Further, a survey of Canadian oncologists found that oncologists were more likely to refer to TPC services when they had completed a rotation in palliative care. 167 Thus, being part of a larger, multidisciplinary team alongside palliative care colleagues allows oncologists to share the burden of complex care delivery, potentially also preventing burnout and compassion fatigue.…”
Section: Educational Barriers and Facilitators For Integration Of Palmentioning
confidence: 99%